Sunan al Tirmidhi wahuwa al jami' al Sahih - Abi 'Isa Muhammad Ibn 'Isa Ibn Surat al Tirmidhi (Dar al Fikr, 1980)
ws.jl.1.c.1-5,jl.2.c.1-3,jl.3.c.1-5,jl.4.c.1-4,jl.5.c.1-5/ir,jl.2,c.4/sgh JIl.1 c6,jil2 c 4,jil3 c 6,jil 4 c 5,jil 5 c 6